Effect of immersion in effervescent granules of watermelon rind (Citrullus lanatus) extract on the surface roughness of artificial teeth - Fransiska, Aria; Sabilla, Alifia; Sari, Desy Purnama; Putri, Fidya Meditia (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Artificial teeth elements are essential components of removable dentures. Inadequate cleaning can lead to the accumulation of microorganisms, which may cause denture stomatitis. Alkaline peroxide effervescent tablets are commonly used denture cleansers. However, prolonged use may increase the surface roughness of artificial teeth. To address this, an alternative natural-based cleanser has been formulated using red watermelon (Citrullus lanatus) rind extract in effervescent granule form. Effervescent granules of watermelon rind extract have potential as an alternative denture cleanser due to their antibacterial properties. The effervescent reaction helps mechanically remove plaque and debris while inhibiting the growth of microorganisms that cause odor and infection. This formulation is practical, natural, and economical. The study aims to evaluate the effect of immersion in effervescent granules containing watermelon rind extract on the surface roughness of artificial teeth. This was a laboratory experimental study using acrylic resin-based artificial teeth. Samples were divided into three treatment groups: aquadest, alkaline peroxide effervescent solution, and watermelon rind effervescent granule solution (n = 5). Surface roughness was measured using a Surface Roughness Tester, and data were analyzed with the Kruskal–Wallis test (p < 0.05). The mean surface roughness values after immersion in aquadest, alkaline peroxide solution, and watermelon rind effervescent granules were 0.140 ± 0.026 µm, 0.616 ± 0.213 µm, and 0.670 ± 0.041 µm, respectively. The findings demonstrate that immersion in effervescent granules containing watermelon rind extract significantly increases the surface roughness of artificial teeth. Further formulation development is recommended to optimize its potential as a natural denture cleanser.